(untitled) (Revista científica Olimpia, 2020)
The investigation was guided to propose a plan of intervention psicopedagógico for the improvement of the interpersonal relationships, the same part of a diagnosis of these variables, specifically: the interactive aspect of the communication, the interpersonal relationships and the state of satisfaction grupal. For the realization of the same one, it was selected a group of methods and techniques among which are: the sociometría, the comunicograma and the questionnaire of state of satisfaction grupal that were applied a population composed by 12 students of 2do year of Agronomy of the University of Granma. The investigation contributed a series of results that they demonstrated the existence of elements disfuncionales in the dynamics of the variable psicosociales of the team in which is carried out the investigation, and the necessity of proposing activities for the improvement of the same ones. The reached results are susceptible of use in the professor’s work for the development of the group.